Psychotherapy for the advanced practice psychiatric nurse : a how-to guide for evidence-based practice - Wheeler, Kathleen, 1947- (Springer Publishing Company, LLC, 2014)
"This is a holistic, evidence-based approach to practicing psychotherapy for both the experienced and neophyte advanced practice nurse. Integrating neuroscience with psychotherapeutic theory, this award-winning text presents clear, step-by-step guidelines for techniques that reflect the wealth of experience garnered by Dr. Wheeler, an APN clinician of many years. The book unites disparate psychotherapeutic approaches into a model that is concise and straightforward, yet sufficiently comprehensive to provide a framework for practice that highlights the most useful models, principles, and techniques of psychotherapy."--Provided by publisher.